Cost-shifting of dialysis treatment in Western Australia: Winners and losers - Mangano, Maria (Centre for Research in Applied Economics, Curtin Business School, 2009)
The process of cost-shifting occurs when surplus revenues from one set of services are used to subsidise another set of services or patient group. In Western Australia the call for increased home dialysis in order to reduce the pressure on the WA health system has been suggested to reduce the burden on hospitals. However, when consideration is given to the increased probability of PD peritonitis (especially among the indigenous population), it is possible that hospitalisation rates may increase, offsetting some of the reduced burden. The privatisation of home dialysis in 2006 created divided treatment regimes for dialysis patients such that this group is disadvantaged when they require hospitalisation for any reason, due to the privatisation of PD nurses and resources. Cost-shifting creates winners and losers, therefore, because it will increase rents to the private company that is the monopoly provider of home dialysis equipment and consumables, while reducing the quality of overall care for PD patients in hospitals.